EVALUASI KUALITAS PENGGUNAAN ANTIBIOTIKA PADA PASIEN PASCA BEDAH DENGAN METODE GYSSENS DI RSUD BDH SURABAYA PERIODE 2016 - Hajar Sugihantoro; Abdul Hakim; Nur Miya Zakiya (Universitas Wahid Hasyim Semarang, 2020)
ABSTRACT The rational use of antibiotics is prescribing antibiotics, dosage, duration, safe and affordable interval of medicine use by the patient. The purpose of this research is to know the quality of antibiotics use to the post-surgery patients in BDH Surabaya for 2016. This is a cross-sectional design, collecting the data from the medical records of post-surgery patients who received antibiotics in BDH Surabaya during 2016. The sample was taken by proportional stratified sampling. The quality of antibiotics use was analyzed by using Gyssens. The result showed that from reviews those 97 medical records, the total of the rational use of antibiotics in BDH Public Hospital Surabaya were 59.7% (category 0) and 40.3% included to the category II-IV. The use of antibiotics with incorrect dosages (category IIA) 4.8%, inappropriate administration intervals (category IIB) 7.7%, too long use (category IIIA) 16.3%, too short use (category IIIB) 1.9%, there was more effective antibiotics (category IVA) 2.9%, and there was other cheaper antibiotics (category IVC) 6.7%. Based on the quality of the use of antibiotics in post-surgical patients in BDH Hospitals at 2016 period, that appropriate Gyssens category rational antibiotic use was 59.7% and the results are not rational as much as 40.3%. Keywords: antibiotic, rational, quality, Gyssens